PENERAPAN WASTE ASSESSMENT MODEL DAN VALUE STREAM ANALYSIS TOOLS UNTUK MENINGKATKAN EFISIENSI DI PT. XYZ - Sima Sebayang; Daniel Sembiring (JURNAL MITRA MANAJEMEN, 2017)
AbstractThis research aims to improve the efficiency of the clean water processing by minimizing waste that occured throughout the entire process where in the actual cannot meet with the customer demand in the amount of 3.800.000 m3 per month, while the average process capacity per month only 87% of demand or around 3.306.000 m3 per month. Lean Manufacturing methods that used in this research are Waste Assessment Model and Value Stream Mapping to identify the waste and Value Stream Analysis Tools to choose the most suitable waste analysis tools. According to the result of waste identification in clean water processing at PT XYZ, 2 wastes with the highest ranking found, the wastes are Processing Waste with the precentage of 27,04% and waiting waste with the percentage of 18,96%. VALSAT Tools which used to minimize the waste in this research is Process Activity Mapping (PAM), and according to the analysis of Process Activity Mapping, we knew that 33,84% of the process is Value Added, 3,91% of the process is Non-Value Added, and 62,25% of the process is Necessary Non-Value Added. According to the analysis result mentioned, 2 recommendations were proposed, which are combine a couple of similar inspection process and add more machine to process the PW-55, Coagulan, and Soda Ash. These recommendations will improve the efficiency of clean water processing at PT XYZ where the Value Added increase from 33,84% to 40,28%, percentage of Non-Value Added increase from 4,51% to 4,83% and the percentage of Necessary Non-Value Added decrease from 61,65% to 54,89%. The time needed in the process is also decreasing from 19.950,3 seconds to 16.760,3 seconds. Keyword : Lean Manufacturing, Waste Assessment Model, Value Stream Analysis Tools, Value Stream Mapping, Process Activity Mapping.